Students’ readiness for the formation of primary schoolchildren’s argumentative skill while identifying the real motive of the action - Shevchenko, Yu.; Zhuravlova, L.; Taranenko, Halyna; Тараненко, Галина Григорівна; Тараненко, Галина Григорьевна; Dubiaha, S. (My University, 2020)
The article deals with the problem of the future teachers training for the formation of argumentation junior pupils’ skills identifying the true motive of an act as an intellectual activity. The specifics of the future teachers’ training in higher education institutions are analyzed; the peculiarities of the process of development of argumentation skills are determined. The prospects for preparing for the formation of junior school students’ argumentation skills in higher educational institutions are outlined. The problem of developing the professional competence of future teachers in the training of junior schoolchildren is substantiated. Their reasoning is grounded because of the argumentation of their behavior and the motive for its implementation. The emphasis is placed on the fact that the readiness of students-future teachers to develop skills of junior pupils’ argumentation is impossible without argumentative competence which is a set of intellectual and communicative skills, and is formed in the process of communication, performing functions of explanation of the statement of assertion or conviction of the interlocutor, and is carried out on the principle’s objectivity, rationality, and dialogue. It has been experimentally proved that argumentative competence as the basis of readiness to develop younger students’ skills of argumentation in identifying the true motive of an act enables the mastery of the relevant techniques and positively affects the professional and personal qualities of the future teacher.
Keywords: argumentation; argumentative and debatable skills; argumentative competence